2013
DOI: 10.1590/s1980-65742013000100004
|View full text |Cite
|
Sign up to set email alerts
|

O Índice de Desenvolvimento Humano e a Data de Nascimento podem condicionar a ascensão de jogadores de Futebol ao alto nível de rendimento?

Abstract: Could the Human Development Index and Birth-Date of the players influence the climbing up to higher performance in Soccer?Abstract: The present study verifies the possible influence of the human development index (HDI) and the birth-date (BD) on the climb up to higher performance in sports, considering Brazilian football context. The sample comprised all 643 players from 20 teams of the Premier Football League in Brazil. The data were collected from official website of Brazilian National Federation, United Nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
11
0
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 30 publications
(22 reference statements)
4
11
0
8
Order By: Relevance
“…These data suggests that RAE can affect the opportunities of access to this level of competition. These results of our study corroborate the literature about RAE on Brazilian elite men futsal 12 , as well as elite men football 20,24 .…”
Section: Men Futsalsupporting
confidence: 91%
See 3 more Smart Citations
“…These data suggests that RAE can affect the opportunities of access to this level of competition. These results of our study corroborate the literature about RAE on Brazilian elite men futsal 12 , as well as elite men football 20,24 .…”
Section: Men Futsalsupporting
confidence: 91%
“…This sport has been presenting RAE in many countries and conditions 20,22,24,25,26,27 . In Brazil, Costa, Cardoso and Garganta 20 have studied senior football players and found that those born in the last quarter of the year have a lower chance to rise on elite level. Between several approaches, literature justifies RAE through maturational issues 26 .…”
Section: Men Futsalmentioning
confidence: 99%
See 2 more Smart Citations
“…futuros jogadores para a modalidade. Evidências científicas acrescentam que a formação de atletas de elite geralmente se inicia em ambientes propícios à experimentação regular de atividades esportivas nos primeiros anos de vida 12. Treinamentos no campo de futebol do DEF.As categorias são fracionadas de acordo com a idade e trabalhadas de maneira apropriada para cada idade específica, pois reconhecemos a importância em adaptar os materiais, espaços físicos e algumas regras, tendo em vista que existem diferenças estruturais, cognitivas, motoras e afetivas entre um adulto, um adolescente e uma criança na participação em atividades esportivas 13.…”
unclassified